Efecto de la inclusión de harina de cascara de cacao sobre los parámetros productivos y características organolépticas de la carne de pollos de engorde Cobb 500 - Bajaña Reyna, Héctor Franklin (2025)
The purpose of this experimental study was to evaluate the effect of cocoa shell meal on the diet of Cobb 500 chickens. The study was conducted at the San José compound in the Baba Canton, Los Ríos province. One hundred Cobb 500 chickens were used, distributed among three treatments and a control group. Each treatment consisted of five replicates, with five birds per replicate. The main objective was to analyze the impact of cocoa shell meal on production parameters such as feed conversion ratio (FCR), weight gain, feed intake, mortality, cost-benefit ratio, and organoleptic characteristics of the meat such as flavor, odor, color, and texture. The treatments evaluated were: T0, which served as a control and did not receive cocoa shell flour in its feed; T1, with 10% cocoa shell flour in the chickens' diet; T2, with 20% cocoa shell flour in the diet; and T3, with 30% cocoa shell flour. Statistical analysis was performed using the InfoStat computer system and the Tukey test at 5%. The best treatment was the following: Weight gain per treatment in grams. Treatment T2 stood out with 3630.20 grams. Regarding feed consumption, it consumed 22858.00 grams, thus ranking second in feed consumption among the treatments. The best treatment in feed consumption was the treatment that did not use cocoa shell flour, T0, with 1.45 grams.